Knowledge and Attitude toward the Therapeutic Potential of Human Amnion Stem Cells among Students of Taif University, Saudi Arabia - Alhomrani, Majid; Alamri, Abdulhakeem S.; Alsanie, Walaa F.; Raafat, Bassem M.; Altalhi, Tariq; Alotaibi, Nujood S.; Algthami, Fay T.; Alsalmi, Reyouf H.; Alhalifi, Najwa H.; Asdaq, Syed Mohammed Basheeruddin; Sreeharsha, Nagaraja (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Among the various types of stem cells which have been suggested for therapeutic purposes, human amnion epithelial cells (hAEC) are highly promising. Purpose: This study aims to assess the knowledge and attitudes of the Taif University population toward the therapeutic potential of hAEC. Methods: This was a cross-sectional study carried out among the students of Taif University. A self-administrated questionnaire was used in this descriptive study. The questionnaire consisted of demographic information, knowledge, and attitudes regarding stem cells and hAEC. The data was analyzed using descriptive statistics in SPSS-IBM 25. Results: Out of 1026 subjects, 908 (88.6%) were female, 686 (66.9%) from the age group of less than 25 years, 984 (96%) Saudi nationals, and 834 (81.45%) were undergraduate students. Unfortunately, 35% of the subjects in this study have no idea about stem cells and 55% have never heard about hAEC. Only a moderate level of knowledge score was noticed among the participants about stem cells. Significantly (P=0.001) high percentage of females would like to conserve their human amniotic epithelial cells for family or for research purposes. More than 88% of the subjects would like to have awareness programs in the community about human amniotic epithelial cells. The knowledge and attitude scores were shown to have a substantial positive association. Conclusion: As a result of this research, it is suggested that various stem cell educational programs and awareness campaigns need to be implemented in universities in order to improve stem cell knowledge and encourage a more positive attitude toward the use of stem cells for therapeutic purposes.
Keywords: Human amniotic epithelial cells; Knowledge; Attitude; Taif University; Awareness campaigns